1996
DOI: 10.1002/lt.500020107
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic allograft rejection: Regulation of the immunogenicity of human intrahepatic biliary epithelial cells

Abstract: lntrahepatic biliary epithelial cells were immunomagnetically purified from specimens of disaggregated human liver and were propagated in vitro. After three passes in culture, the cells were shown to be over 85% pure with contaminating leukocytes and endothelial cells constituting less than 2% of the population. Sensitive flow microfluorimetric analysis was performed after immunofluorescence labeling to quantify expression of both class I and class II major histocompatibility (MHC) antigens and the adhesion mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The up-regulation of adhesion molecule expression produced by culturing endothelial or consistent with results from previous studies [6,7]. It is reasonable to assume that flow-cytometric detection of elevated adhesion molecule expression by parenchymal cells would be associated with a concomitant increase in the adhesion of activated T-lymphocytes.…”
Section: Resultssupporting
confidence: 80%
“…The up-regulation of adhesion molecule expression produced by culturing endothelial or consistent with results from previous studies [6,7]. It is reasonable to assume that flow-cytometric detection of elevated adhesion molecule expression by parenchymal cells would be associated with a concomitant increase in the adhesion of activated T-lymphocytes.…”
Section: Resultssupporting
confidence: 80%
“…Primary antibodies for intracellular staining were directed to cytokeratin 7 and 19 (Dako, A/S, Denmark). For labelling of intracellular antigens,21 cells were pelleted and washed once in 300 μl of PBS containing 0.5% (w/v) saponin (Sigma). Primary antibodies at predetermined concentrations were added to the cells and incubated for 30 minutes at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Also, the same virus appears to reduce the rate of IFN-γ induced de novo expression of HLA class II, leaving unaffected HLA class I 115 . Data have shown that cytokine-induced expression of adhesion molecules such as intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1), and lymphocyte function-associated antigen-3 (LFA-3) of human BECs is comparable to that seen in Epstein-Barr virus-transformed B-cell lines, a known antigen presenting cell 117 . The expression of these adhesion molecules is a prerequisite for effector cells to exert their cytolytic action 118 .…”
Section: Liver-related Antigen Presenting Cells In Immunity and Tolermentioning
confidence: 99%